An Indispensable Utopia of Values. Axiological Significance of Utopian Thinking - Łukaszewska , Katarzyna (Studia Ecologiae et Bioethicae, 2020)
Utopia is indispensable for man - it is thought-provoking, challenging, and it defies the impossible. Thanks to absolutisation, the ability to reflect determines the direction of development, its dimension and meaning. For axiology, utopia provides the basis for putting absolute values into practice, even if the process of their cognition is based on a special kind of autonomous and intuitive self-commitment. We cannot be compelled to pursue values, but we can be inspired to cherish them by the example of personal involvement in an axiological utopia, opening us up to non-relativity, immeasurability, moderation, and sustainability in development. The utopia of values brings us closer to the existence of something that is not solely relative, dependent, conditioned. The theory of absolute values explains the utopian sense of creating a harmonised hierarchy of values, and seeking objective valuations, serving not only the concept of sustainable development but the broadly understood idea of the common good, the community effort.